(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper is outcome of review of various research studies carried out on E- commerce. it examines different opportunities of E-retailing, E-commerce, E-learning ,E- education and E-financing. E-commerce as anything that involves an online transaction. E-commerce provides multiple benefits to the consumers in form of availability of goods at lower cost, wider choice and saves time. E-commerce can be broken down into two parts: E-merchandise: E-finance. E commerce involves conducting business using modern communication instruments: telephone, fax, e-payment, money transfer systems, e-data interchange and the Internet. Online businesses like financial services, travel, entertainment, and groceries are all likely to grow. Forces influencing the distribution of global e-commerce and its forms include economic factors, political factors, cultural factors and supranational institutions. Many companies, organizations, and communities in India are beginning to take advantage of the potential of e-commerce; critical challenges remain to be overcome before e-commerce would become an asset for common people.